Change leadership : a practical guide to transforming our schools - Wagner, Tony.; Kegan, Robert (San Francisco : Jossey-Bass, 2006)
Offers education leaders practical advice and strategies to help them transform their schools into effective, accountable institutions better able to cope with the challenges schools face in the twenty-first century.
Includes bibliographical references
Keywords: School management and organization -- United states; Education -- Aims and objectives -- United States; Educational change -- United States